KARAKTERISTIK TENAGA KERJA INDONESIA MENJELANG ERA BONUS DEMOGRAFI - Heryani, Heryani; Siagian, Tiodora Hadumaon (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2023)
Based on the results of the 2020 population census, Indonesia's population is 275 million people. As many as 62.28 percent are productive age. This research will study the relationship between the peak of the demographic dividend and workforce characteristics. Data from the Statistics of Indonesia will be analyzed descriptively related to the data presented in the tables and graphs. The productive age population in Indonesia is more than 90 percent of the working population. This population is a population whose highest education is elementary school graduates and below. This will threaten Indonesia as it approaches the peak of the demographic dividend, expected to occur in 2030. Not only low education workforce but also business fields in the agricultural sector with self-employed status. Characteristics of Indonesia's poor characterize this phenomenon. In Indonesia's poor population, more than 50 percent of education is completed in elementary school and below. In addition, the primary source of income comes from the agricultural sector. To overcome this, the solution is for those with primary education to be forced to continue their formal education. However, training and courses can be provided to enhance their skills. The government also needs to increase employment opportunities for the Indonesian population.